2016
DOI: 10.5625/lar.2016.32.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of essential oil ofEucalyptus globulusagainst fish pathogenic bacteria

Abstract: The antibacterial activities of the essential oil of Eucalyptus globulus (EOEG) was determined against 7 fish pathogenic bacteria (Edwardsiella tarda, Streptococcus iniae, S. parauberis, Lactococcus garviae, Vibrio harveyi, V. ichthyoenteri and Photobacterium damselae) obtained from farmed olive flounder. The inhibitory activity was evaluated by three methods: Disc diffusion method, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). According to the disc diffusion test, as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…A wide range of phytochemicals has been reported from E. globulus previously (Gouveia et al, 2012). In this study, eucalyptol and 1R-α-Pinene were found to be major components of E. globulus which is consistent with previous studies as well which also agrees that antimicrobial activity of E. globulus can be due to α-pinene and eucalyptol(1,8-cineole) components present in the oil (Mekonnen et al, 2016;Park et al, 2016). Conclusions: It is concluded that essential oils of C. zeylanicum and E. globulus have diverse phyto-constituents and profound in vitro activity against Salmonella enteritidis and Salmonella gallinarum of poultry origin.…”
Section: Discussionsupporting
confidence: 91%
“…A wide range of phytochemicals has been reported from E. globulus previously (Gouveia et al, 2012). In this study, eucalyptol and 1R-α-Pinene were found to be major components of E. globulus which is consistent with previous studies as well which also agrees that antimicrobial activity of E. globulus can be due to α-pinene and eucalyptol(1,8-cineole) components present in the oil (Mekonnen et al, 2016;Park et al, 2016). Conclusions: It is concluded that essential oils of C. zeylanicum and E. globulus have diverse phyto-constituents and profound in vitro activity against Salmonella enteritidis and Salmonella gallinarum of poultry origin.…”
Section: Discussionsupporting
confidence: 91%
“…Antimicrobials have been used for a long time to treat different bacterial infections, but the frequent use of these antimicrobials has resulted in growing antimicrobial resistance. Meanwhile, the essential oils have been shown strong antimicrobial activity against these pathogenic bacteria [ 20 21 ]. Therefore, the current study was conducted to determine the efficacy of EOL against pet turtle-borne bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its main component 1,8-cineneol has been used in products for oral hygiene, such as Listerine Cleanmint (Pfizer), Listerine Freshmint (Pgizer), and Walgreens Fresh Breath Antiseptic Mouth Rinse (Walgreen Co.) [99]. The EO was also active against E. tarda, V. ichthoenteri, V. harveyi, P. damselae, S. iniae, S. parauberis, and L. garviae , considered to be pathogens of fish [100]. Furthermore, it exhibits toxic effects against S. aureus and E. coli [101].…”
Section: Description Of Eosmentioning
confidence: 99%